2022
DOI: 10.3390/membranes12111070
|View full text |Cite
|
Sign up to set email alerts
|

A Summary of Practical Considerations for the Application of the Steric Exclusion Chromatography for the Purification of the Orf Viral Vector

Abstract: Steric exclusion chromatography (SXC) is a promising purification method for biological macromolecules such as the Orf virus (ORFV) vector. The method’s principle is closely related to conventional polyethylene glycol (PEG) precipitation, repeatedly implementing membranes as porous chromatographic media. In the past decade, several purification tasks with SXC showed exceptionally high yields and a high impurity removal. However, the effect of varying process parameters, on the precipitation success and its lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 46 publications
3
22
0
Order By: Relevance
“…Infectious LV recovery was significantly higher ( p ≤ 0.01) when internal mixing was performed ( Figure 3 C) than when external mixing was performed (73.94 ± 12.13% and 24.53 ± 13.43%, respectively). These findings support the results of Labisch et al and Eilts et al, in which the same effect was observed for other module sizes [ 10 , 13 ]. Moreover, a significantly higher amount of LVs (38.05 ± 12.37%) was lost in the flow through ( p ≤ 0.05) when LVs were loaded after external mixing.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Infectious LV recovery was significantly higher ( p ≤ 0.01) when internal mixing was performed ( Figure 3 C) than when external mixing was performed (73.94 ± 12.13% and 24.53 ± 13.43%, respectively). These findings support the results of Labisch et al and Eilts et al, in which the same effect was observed for other module sizes [ 10 , 13 ]. Moreover, a significantly higher amount of LVs (38.05 ± 12.37%) was lost in the flow through ( p ≤ 0.05) when LVs were loaded after external mixing.…”
Section: Resultssupporting
confidence: 92%
“…Since the average pore diameter remains unchanged, the flow velocity inside the pores decreases and falls below the optimal flow velocity inside the stationary phase to achieve efficient LV capture during loading and release during elution. Another possible explanation, recently discussed in [ 13 ], is that a limited spontaneous encounter for the LV and the stationary phase could lead to a less efficient depletion interaction. In our case, a certain flow rate through the membrane pores might be necessary to increase the probability of an encounter between the LVs and the stationary phase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings were reported before for Orf virus (Eilts, Lothert, Orbay et al, 2022) and for latex particles (Eilts, Steger, Lothert & Wolff, 2022b). However, the final precipitate sizes were expected to vary between the static experiments and the dynamic SXC runs.…”
Section: Precipitation Of Khv In the Sxc Processsupporting
confidence: 91%
“…Time-dependent size measurements of the KHV-containing cell culture supernatant were conducted via dynamic light scattering, adapted from Eilts, Lothert, Orbay et al (2022). Therefore, clarified virus suspension was mixed in equal parts with CPB (15 mS cm −1 ) of a defined pH (4-7.4) and PEG-6000-concentration (Carl Roth) (0%-12%).…”
Section: Precipitation Behaviour In Dependence Of Peg Concentration A...mentioning
confidence: 99%